Lure-and-Kill Yeast Interfering RNA Larvicides Targeting Neural Genes in the Human Disease Vector Mosquito Aedes aegypti. Issue 1 (December 2017) - Hapairai, Limb; Mysore, Keshava; Chen, Yingying; Harper, Elizabeth; Scheel, Max; Lesnik, Alexandra; Sun, Longhua; Severson, David; Wei, Na; Duman-Scheel, Molly
Abstract New mosquito control strategies are vitally needed to address established arthropod-borne infectious diseases such as dengue and yellow fever and emerging diseases such as Zika and chikungunya, all of which are transmitted by the disease vector mosquitoAedes aegypti . In this investigation, Saccharomyces cerevisiae (baker's yeast) was engineered to produce short hairpin RNAs (shRNAs) corresponding to theAedes aegypti orthologs offasciculation and elongation protein zeta 2 (fez2 ) andleukocyte receptor cluster (lrc ) member, two genes identified in a recent screen forA .aegypti larval lethal genes. FeedingA .aegypti with the engineered yeasts resulted in silenced target gene expression, disrupted neural development, and highly significant larval mortality. Larvicidal activities were retained following heat inactivation and drying of the yeast into tabular formulations that induced >95% mortality and were found to attract adult females to oviposit. These ready-to-use inactivated yeast interfering RNA tablets may one day facilitate the seamless integration of this new class of lure-and-kill species-specific biorational mosquito larvicides into integrated mosquito control programs.